2019
DOI: 10.14738/abr.79.6640
|View full text |Cite
|
Sign up to set email alerts
|

Testing for Weak-Form Market Efficiency in the Botswana Stock Market

Abstract: The theory of the Efficient Market Hypothesis (EMH) has been debated extensively. In this study the runs test was employed on the Botswana Stock Exchange daily Domestic Companies and Foreign Companies indices to test whether the Botswana stock market follows the random walk process and subsequently determine weak-form market efficiency. The results of the runs test showed that the indices do not follow the random walk process. As a result the Botswana stock market is determined to be weak-form market inefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…These findings imply that prices do not fully reflect the information available and that changes in prices are not independent and identically distributed. These findings are in line with the evidence suggested by the authors Atac and Tas (2019), Olubiyi and Olopade (2019), Mphoeng (2019) that show inefficiency, in its weak form, which allows investors to have abnormal gains without incurring increased risk. Source: Own elaboration…”
Section: Source: Own Elaborationsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings imply that prices do not fully reflect the information available and that changes in prices are not independent and identically distributed. These findings are in line with the evidence suggested by the authors Atac and Tas (2019), Olubiyi and Olopade (2019), Mphoeng (2019) that show inefficiency, in its weak form, which allows investors to have abnormal gains without incurring increased risk. Source: Own elaboration…”
Section: Source: Own Elaborationsupporting
confidence: 92%
“…Chaker and Sabah (2018) tested the efficiency, in their weak form, in the markets of the United Arad Emirates (UAE), Saudi Arabia, Oman, Kuwait and Bahrain, showing that none of the analysed markets follow the random walk hypothesis. Atac and Tas (2019), Olubiyi and Olopade (2019), Mphoeng (2019) examined the market efficiency, in its weak form. Atac and Tas (2019) investigated the Istanbul stock exchange, and have shown that the efficiency hypothesis is rejected.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The results suggest that none of the five stock markets follow the random walk hypothesis. Mphoeng (2019), Pernagallo and Torrisi (2019), Malafeyev, Awasthi, S. Kambekar, and Kupinskaya (2019), tested efficiency, in its weak form, and tested whether markets are predictable. Mphoeng (2019) tested the efficient market hypothesis in the Botswana stock market, showing that the random walk hypothesis was rejected, which maintains that the market is inefficient in the analysed period.…”
Section: Literature Revisionmentioning
confidence: 99%
“…Mphoeng (2019), Pernagallo and Torrisi (2019), Malafeyev, Awasthi, S. Kambekar, and Kupinskaya (2019), tested efficiency, in its weak form, and tested whether markets are predictable. Mphoeng (2019) tested the efficient market hypothesis in the Botswana stock market, showing that the random walk hypothesis was rejected, which maintains that the market is inefficient in the analysed period. Pernagallo and Torrisi (2019) analysed whether the behaviour of the daily returns of the stock market indexes of 12 emerging economies corroborates the hypothesis of "fat tails" and whether these series show long memory.…”
Section: Literature Revisionmentioning
confidence: 99%